KINETICS OF THE ACETYLCHOLINESTERASE (AchE) INHIBITION - Hendry Yanuar (Universitas Gadjah Mada, 2001)
Acetylcholinesterase (AchE) is an enzyme, which work on acetylcholine hydrolysis. Some insecticides can inhibit the activities of this enzyme. The purpose of this research was determined the kinetics of the AchE inhibition over the organophosphate and carbamat inhibitors with the methylindoxylacetate (MIA) as a substrate. The AchE extract was obtained from the local honeybee head (100 heads on the 5 mL of phosphate buffer 0.05 M). Based on the preliminary analysis, the volume of the enzyme extract for the reaction rate was 100 mL on 1-5 mL of the substrate. Monocrothopos, Carbophenathion, Baycarb and MIPC were used as inhibitors which the concentration were 0.0018, 0.0030, and 0.0042 mg/mL respectively. The reaction rate were measured by Fluorescence HPLC Monitor (Shimadzu RF 535) at 540 nm, and some computational program were used on data analysis. The result of this research showed that the maximum rate of MIA hydrolysis by AchE without the presence of inhibitor was 5.16 mL/s and the hydrolysis constant (Km) was 3.49, and the inhibitors did not influence the maximum rate of substrate hydrolysis. It was finally concluded that the kinetics of AchE inhibition on MIA hydrolysis over the organophosphate and carbamat inhibitors was the competitive inhibition.